Medicinal cupping in the eyes of graph theory - Yuhani, Yusof; Nurfatihah, Mohamad Hanafi; Mohd Sham, Mohamad; Muhammad Faiz, Abu Bakar; Mohd Addha, Ibrahim (Penerbit UMP, 2020)
Medicinal cupping is one of the traditional treatment methods that is trusted to give many benefits to the human health and still practising by various culture and societies around the world. The purposes of this treatment are to allow the toxin leaves the body,to stimulate the muscles and also helping in healing process for various diseases. The process start by placing special heated cups on specific points to create suction, then the points will be punctured. Each disease has specific cupping points to be cupped which located on the human nerves system. All the points actually connected to each other where a simple graph can be formed. Since there are limited studies that discuss medicinal cupping in a mathematics view, thus this research is conducted to introduce the easiest way on demonstrating the cupping points on the human nerves system by using the idea of graph. Hence, new definition of nerve vertex, nerve edge and nerve graph will be defined. Moreover, the idea of graph colouring will be applied to determine the optimal number of cupping points.